1999
DOI: 10.1046/j.1420-9101.1999.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of natural populations of Castanea sativa in Turkey: evidence of a hybrid zone

Abstract: This study points out the evidence of a hybrid zone between two groups of genetically differentiated populations of chestnut (Castanea sativa Mill.) in Turkey. Genetic structure, gene flow and introgression levels, based on 16 allozyme loci, were investigated on 34 population samples spanning the entire C. Sativa distribution area in this country. The occurrence of the hybrid zone, located in the Bithynian region, was inferred in a group of populations showing the following genetic characteristics: (i) enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…Taking Turkey as one of the supposed centres of origin of the European chestnut, Villani et al (1992Villani et al ( , 1994Villani et al ( , 1999 confirmed genetic, morphological and physiological differentiation among wild chestnut populations spread along a Turkish transect spanning from the Black Sea coast to the Mediterranean area. Genetic differentiation of these populations was associated with macroclimatic variables, specifically, with amount of rainfall (Pigliucci et al, 1990).…”
Section: Discussionmentioning
confidence: 73%
“…Taking Turkey as one of the supposed centres of origin of the European chestnut, Villani et al (1992Villani et al ( , 1994Villani et al ( , 1999 confirmed genetic, morphological and physiological differentiation among wild chestnut populations spread along a Turkish transect spanning from the Black Sea coast to the Mediterranean area. Genetic differentiation of these populations was associated with macroclimatic variables, specifically, with amount of rainfall (Pigliucci et al, 1990).…”
Section: Discussionmentioning
confidence: 73%
“…It is probable that Greek colonists introduced chestnut cultivation to the Italian peninsula, making use of tree varieties from the main chestnut zones of Ancient Greece, just as they did for grapevine (Dion 1977). This hypothesis is partly supported by the observation that the current chestnut populations of the western Anatolian peninsula are genetically more similar to Italian and French populations than to the chestnut groves of eastern Anatolia facing the Black Sea (Villani et al 1999), even though the phylogenetic map of the chestnut in Europe is not fully understood yet (Fineschi et al 2000). There is indirect etymological evidence for the hypothesis that the first chestnut growing in the Italian peninsula had an early Greek origin and that the Latin world had early contact with chestnut cultivation.…”
Section: Transmission To the Latin Worldmentioning
confidence: 90%
“…Once all genetic marker data in clinal situations are available, the disequilibria between cytoplasmic and nuclear genes, in fact, can be tested using the methods introduced by Basten and Asmussen (1997). Characteristic length can also be estimated, as demonstrated in one typical dispersal-selection cline recently reported in Castanea sativa Mill (Villani et al, 1999). If the ratio of pollen to seed flow can be approximately estimated by using neutral markers (Ennos, 1994), equations (5) or (11) provides a convenient way to estimate the relative selection coefficients between cytoplasmic and nuclear genes.…”
Section: Discussionmentioning
confidence: 99%